Sexuality of Jung Bahadur Rana - K C, Tej Bahadur (Academia Research Journal, 2023)
The article focused on Jung Bahadur Rana, the Prime Minister of a period in the history of modern Nepal and his activities. Many activities of Janga Bahadur have become the subject of history. Some of Jung Bahadur's activities made him immortal, while others made him notorious. Among his activities, the main activity is his sexual attraction to heterosexuals. The presented article focuses on the theme of sexual activity of this Jung Bahadur. In particular, the purpose of this article is to expose what kind of sexual activities Jung Bahadur did during his lifetime. Jung Bahadur's bravery and courage earned him much respect, but his attachment to women had a negative effect on it. Although it is said that Jung Bahadur had infinite courage and determination, he could not control his sexual weakness. Jung Bahadur Rana's uncontrollable sexual activities became the subject of broadcast even in foreign media. Some of his sexual activities were outstanding. They used to bring many beautiful women in the palace and also appointed employees for their movement. Among his means of entertainment, sex was the most preferred subject. He wanted to show himself to be good at sex. It is the law of nature that sexual desire and sexual activity decrease as people get older due to increasing age, busyness of politics and other reasons. Unable to understand this matter, Junga Bahadur felt that he was weak in his sexual addiction even though he was an old man and started taking opium. The purpose of this article is to investigate the sexual desire of Junga Bahadur Rana by exposing the fact that from time to time he used to be self-condemned and sometimes he used to be very depressed.